Controllable synthesis and tunable colors of a- And -Zn 2SiO4:Mn2+ nanocrystals for UV and blue chip excited white LEDs - Ye, R.; Jia, Guohua; Deng, D.; Hua, Y.; Cui, Z.; Zhao, S.; Huang, L.; Wang, H.; Li, C.; Xu, S. (American Chemical Society, 2011)
Green- and yellow-emitting a- and ß-Zn2SiO 4:Mn2+ nanocrystals incorporated into glass ceramics have been selectively synthesized successfully by a conventional melt-quenching method. XRD, EPR, TEM, EDS, and electronic optical spectroscopy were employed to discriminate the formation of a- and ß-Zn2SiO 4:Mn2+ nanocrystals and further to elucidate the coordination environment of Mn2+ in the yellow-emitting Zn 2SiO4:Mn2+ practical material. The combination of crystal field calculation with the experimental absorption and excitation spectra enables us to interpret optical spectroscopic features and therefore correlate the optical spectroscopy to the corresponding crystal structure. This work exemplified the correlation between the optical spectroscopy and coordination around the Mn2+ ion and also shed light on the application of glass ceramics containing a- and ß-Zn 2SiO4:Mn2+ nanocrystals for UV and blue chip excited white LEDs. © 2011 American Chemical Society.